2012
DOI: 10.1016/j.chemosphere.2012.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and pathways for the debromination of polybrominated diphenyl ethers by bimetallic and nanoscale zerovalent iron: Effects of particle properties and catalyst

Abstract: Polybrominated diphenyl ethers (PBDEs) are recognized as a new class of widely-distributed and persistent contaminants for which effective treatment and remediation technologies are needed. In this study, two kinds of commercially available nanoscale Fe° slurries (Nanofer N25 and N25S), a freeze-dried laboratory-synthesized Fe° nanoparticle (nZVI), and their palladized forms were used to investigate the effect of particle properties and catalyst on PBDE debromination kinetics and pathways. Nanofers and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(32 citation statements)
references
References 30 publications
8
24
0
Order By: Relevance
“…The removal efficiency of BDE209 in the presence of Pd was more than 3.5 times higher than that without Pd, indicating the engagement of Pd (presumably as a catalyst) in the degradation. This result also agreed with other reports in which rapid dehalogenation occurred in the presence of catalyst Pd [16,17,19]. In addition to potential catalysis by Pd, the large surface area of nanoparticles is also expected to contribute to the removal of PBDEs [28].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The removal efficiency of BDE209 in the presence of Pd was more than 3.5 times higher than that without Pd, indicating the engagement of Pd (presumably as a catalyst) in the degradation. This result also agreed with other reports in which rapid dehalogenation occurred in the presence of catalyst Pd [16,17,19]. In addition to potential catalysis by Pd, the large surface area of nanoparticles is also expected to contribute to the removal of PBDEs [28].…”
Section: Discussionsupporting
confidence: 82%
“…Rapid removal of BDE209 was observed, similar to the results from the acetone/water system [19]. The removal efficiency of BDE209 in the presence of Pd was more than 3.5 times higher than that without Pd, indicating the engagement of Pd (presumably as a catalyst) in the degradation.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Recent studies showed that zero-valent iron (ZVI) could reductively transform TBBPA, decaBDE and HBCD, and that the reduction rates tended to increase with increasing surface area of ZVI (Keum and Li, 2005;Lin et al, 2012;Tso and Shih, 2014;Yu et al, 2012;Zhuang et al, 2012). Bimetallic nanoparticles (such as Ni/Fe, Pd/Fe and Ag/Fe) were also reported to be able to rapidly debrominate either TBBPA or decaBDE (Fang et al, 2011;Huang et al, 2013;Luo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%